Penilaian Tingkat Keberlanjutan Kawasan Wisata Alam Lolai, Kabupaten Toraja Utara - Yultina Tiku Tasik; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
Lolai is a new tourism development area in the last two years in North Toraja Regency. The significant increase in the number of Lolai tourists can have a negative impact on the surrounding environment and the sustainability of the ecosystem in it. This study aims to determine the level of sustainability of the natural tourism area of ​​Lolai based on economic, social and environmental aspects, as well as to identify the determining factors that influence it. This research was conducted from December 2019 to May 2020. This research is located in To`tombi, Bukit Nato, and Tongkonan Lempe which are tourist attractions in the Lolai area. Data collection was carried out through observation, documentation, interviews, distribution of questionnaires, literature study and through related agencies. The analytical method used is descriptive qualitative and quantitative methods supported by the rapfish application in the Multi-Dimensional Scaling (MDS) model and leverage, as well as prospective analysis. The results showed that overall the three tourist objects were in the less sustainable category. In To'tombi tourism object, the economic aspect is quite sustainable, while the social and environmental aspects are less sustainable. In Nato Hill, the economic, social, and environmental aspects are classified as less sustainable. In Tongkonan Lempe, the economic aspect is quite sustainable, while the social and environmental aspects are in the less sustainable category. The main factors that affect the assessment of the sustainability of the natural tourism area of ​​Lolai are access for local communities and community participation (economic aspects), visitor satisfaction (social aspects), and processing of liquid waste and reducing solid waste (environmental aspects).